PENANGGULANGAN KEKERASAN TERHADAP ANAK - Netty Mewahaty Simbolon; Merry N. Sinaga; Mhd. Fadly Nasution (LPPM STIH Awang Long, 2025)
This research aims to determine the countermeasures against violence targeting children. Child protection encompasses all activities to guarantee and protect children and their rights so they can live, grow, develop, and participate optimally in accordance with human dignity. The research method used in this study is a qualitative approach with a normative legal research perspective. Data collection methods include literature studies and documentation. Data analysis was conducted by synthesizing the results obtained from data collection and connecting them to derive answers to the research objectives. Criminal legal sanctions for violence against children are regulated in Law No. 35 of 2014 concerning the Amendment to Law No. 23 of 2002 on Child Protection, Law No. 17 of 2016 concerning the Stipulation of Government Regulation in Lieu of Law No. 1 of 2016 concerning the Second Amendment to Law No. 23 of 2002 on Child Protection into Law, as well as the application of criminal sanctions regulated in the Indonesian Criminal Code (KUHP) regarding maltreatment. Crime prevention efforts are carried out by reducing factors that can lead to crimes against children, namely through preventive and repressive countermeasures. Preventive efforts are crime prevention measures outside of criminal law aimed at preventing the occurrence of child abuse. Repressive efforts are conceptual crime prevention measures taken after the crime has occurred through law enforcement against those involved in criminal acts to prosecute perpetrators of child abuse in accordance with their actions.